Internationalization of two faculty‐based journals at UM: the case of MJCS and MJLIS - Zainab, A.N. (2009)
The term internalization is defined as the process of integrating international standard dimensions into the governance, process and delivery of scholarly journals. The dimensions include such issues as the documented objectives of the journal, the governance of the editorial and reviewing board, the process of publishing, the delivery and distribution of published issues both print or electronic and the indexation status. The journals in this context refer to the Malaysian Journal of Library & Information Science and Malaysian Journal of Computer Science, both published by the Faculty of Computer Science and Information Technology, University of Malaya. These two journals are the first faculty based Malaysian journals that are being currently indexed by the ISI Social Science Citation Index and the Science Citation Index as well as by Scopus since their 2007 issues. This paper traces the beginnings of both journals, especially in their attempts to make themselves visible nationally and international and steps taken to ensure that the journals assimilate the basic attributes needed to gain international standard. The issues that come with this status will also be highlighted.